Consumer Behavior and Marketing Development Strategies for Organic Pork in Thailand - Thuannadee, Angsuthon (Journal of Applied Economics and Management Strategy, 2025)
Currently, consumers are increasingly concerned about health and safety from meat consumption, making organic pork a new alternative that has gained attention. However, there are limitations in production and product accessibility. This study aimed to analyze factors influencing the decision to consume organic pork, as well as to study appropriate marketing management strategies for developing the organic pork market. Data collection involved surveying 400 consumers using questionnaires and interviewing stakeholders in the organic pork supply chain. The analysis was divided into three parts: consumer behavior analysis using descriptive statistics, analysis of factors influencing purchasing decisions using a Binary Logit Model and a Linear Regression Model, and marketing analysis using SWOT and TOWS Matrix. The results showed that although most consumers were aware of organic pork, only a small proportion had consumed it. Consumers perceived the value, safety, and environmental benefits of organic pork but lacked understanding of the impact of hormones in production. The analysis of factors influencing purchasing decisions revealed that age, education, product perception, and household’s consumption behavior of pesticide-free food significantly affected the decision. Additionally, production standards and brand influenced both consumers with and without prior consumption experience, with the former prioritizing pork characteristics and the latter considering product appearance. For market development, strategies should focus on building a credible brand, emphasizing health, environmental, and animal welfare selling points, while promoting farmer groups, developing certification systems, and planning comprehensive marketing for the long-term sustainability of the production system and market.